Recursive expected conditional value at risk in the fleet renewal problem with alternative fuel vehicles. (April 2016) - Ansaripoor, Amir H.; Oliveira, Fernando S.; Liret, Anne
Highlights: A novel risk-based fleet management system is presented. We propose a recursive dynamic risk measure. We study how clustering affects risk management. A case study for a large UK based firm is investigated. Abstract: We study the fleet portfolio management problem faced by a firm deciding which alternative fuel vehicles (AFVs) to choose for its fleet to minimise the weighted average of cost and risk, in a stochastic multi-period setting. We consider different types of technology and vehicles with heterogeneous capabilities. We propose a new time consistent recursive risk measure, the Recursive Expected Conditional Value at Risk (RECVaR), which we prove to be coherent. We then solve the problem for a large UK based company, reporting how the optimal policies are affected by risk aversion and by the clustering for each type of vehicle.